"A bit of everything": Health literacy interventions in chronic conditions – a systematic review. Issue 10 (October 2022) - Larsen, Marie H.; Mengshoel, Anne Marit; Andersen, Marit H.; Borge, Christine R.; Ahlsen, Birgitte; Dahl, Kari Gire; Eik, Hedda; Holmen, Heidi; Lerdal, Anners; Mariussen, Kari L.; Thoresen, Lisbeth; Tschamper, Merete K.; et al.
Abstract: Objective: To systematically evaluate health literacy (HL) interventions in chronic conditions by exploring theoretical perspectives, intervention content and effectiveness. Method: We searched MEDLINE, Cochrane, CINAHL, EMBASE, ERIC, Web of Science and PsycINFO. Standardised systematic review methods were used, and sequences informing our research question were extracted and analysed. The study includes a descriptive summary of the included papers. Results: We included 39 unique interventions, with diabetes and heart disease as the most targeted chronic conditions. Fifty-four percent of papers included a definition of HL, but the studies showed significant heterogeneity of theoretical underpinnings, modes, measures and content. We identified 23 HL measures, mostly assessing functional HL. The HL interventions were often more complex than the measures indicated. A significant change in HL was found in 28 studies. Study quality was generally poor. Conclusions: Interventions optimizing HL appear important to improve health outcomes in chronic conditions. To ensure cumulative knowledge development of this field we need theory-based interventions, consistency in methods and more tailored and comprehensive measures to capture the interventions' complexity. Practice implications: A more valid understanding of HL interventions and measurements is needed to reach an agreed understanding of their components and intentions. Highlights: Health literacy (HL) interventions often lack a definition of HL and theoretical clarifications. Most HL interventions in chronic care lack consistency between theory, content and outcomes (within and between studies). There is a need to develop a valid definition of HL when developing HL interventions in chronic conditions . A broader system approach is needed when developing HL interventions in chronic conditions .